KYAI LEADERSHIP STYLE IN DEVELOPING THE MAJELIS TAKLIM IN ISLAMIC BOARDING SCHOOL - M Rizkoni Salis (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2020)
The purpose of this study was to determine the kyai leadership style in developing the majelis taklim Islamic Boarding School Ar-Rahmah Sleman Yogyakarta. This study uses a qualitative method using descriptive analysis. At the same time, this type of research approach is a case study or field research oriented towards collecting data in the field. Data collection techniques were carried out using observation and interviews. The observation is used to determine the ongoing program of activities, leadership styles and activities with members of the majelis taklim. At the same time, interviews were conducted with 20 informants from the board of foundations and members of the majelis taklim. The results showed that the Kyai leadership style in developing the majelis taklim Islamic Boarding School Ar-Rahmah Sleman Yogyakarta uses a democratic leadership style with indicators that include: The leader makes plans together with members, evaluates ongoing programs, decision making is carried out based on deliberation, respecting the ability or potential of members, the familiarity of the leader with the members without any distance like siblings, having good communication, being able to provide motivation, provide protection, input, guidance, and direction to members to carry out their duties better.